Molecular electronic-structure theory - Helgaker, Trygve; Jørgensen, Poul 1944-; Olsen, Jeppe (Wiley-Blackwell, 2012)
Ab initio quantum chemistry is increasingly paired with computational methods to solve intractable problems in chemistry and molecular physics. Now in a paperback edition, this comprehensive and technical work covers all the important aspects of modern molecular electronic-structure theory, clearly explaining quantum-mechanical methods and applications to molecular equilibrium structure, atomization energies, and reaction enthalpies. Extensive numerical examples illustrate each method described. An excellent resource..